¿Cambio cultural, posible o imposible? Orientaciones para el estudio de la Cultura Organizacional en la Administración Pública Mexicana (Cultural change, is it possible or impossible? Perspectives to study organizational culture in the Mexican public administration) - Mendoza Gómez, Joel (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract: This paper outlines the study of organizational culture and its changes in a context of public administration through the analysis of the implementation of civil service in the Mexican Public Administration. This conceptual development is elaborated to establish some explanations about the link between organizational culture and public administration. By analyzing this link, we establish the relevance of a theoretical approach to study organizational culture and its changes; thus, the influence of organizational culture on individual behavior in the organization is identified.